Rights of an arrested person / Nor'Ain Mohamad Nasir - Mohamad Nasir, Nor'Ain (Faculty of Law, 1986)
Malaysia gained her independence from Britain in 1957.Together with that, Malaysia adopted a form of government by which the supreme law of the land was the written constitution. Part II of this instrument dealt with fundamental liberties. since then, it has been wondered by both lawyers and laymen, to what extent the court would be willing to implement such right. The first case which appeared before the High Court, Chia Khin Sze v. The Menteri Besar of selangor,1 made the legal world hold its breadth with expectation.However, all high hopes were disappointed. A restrictive interpretation to the Constitution was given by the Court and this reduced it to be a mere declaratory function.